2018
DOI: 10.1093/jas/sky028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lemon leaves on energy and C–N balances, methane emission, and milk performance in Murciano-Granadina dairy goats

Abstract: The objective of this experiment was to find out the effect of lemon leaves on energy and C-N balances, methane emission, and milk performance in dairy goats. Lemon leaves were used to replace alfalfa as forage in a diet for Murciano-Granadina goats. Ten Murciano-Granadina dairy goats (44.1 ± 4.47 kg of BW) in late lactation (185 ± 7.2 d) were selected in a crossover design experiment, where each goat received 2 treatments in 2 periods. One group was fed a mixed ration with 450 g of pelleted alfalfa per kilogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Therefore, energetically, goats fed these diets metabolize more feed carbon to milk production than goats fed mixed diets with alfalfa hay as forage from the study of Just et al [29]; 16%. However, the ratio between milk N output and N ingested was similar between diets and with the study of Fernández et al [30]; 22%.…”
Section: Resultssupporting
confidence: 86%
“…Therefore, energetically, goats fed these diets metabolize more feed carbon to milk production than goats fed mixed diets with alfalfa hay as forage from the study of Just et al [29]; 16%. However, the ratio between milk N output and N ingested was similar between diets and with the study of Fernández et al [30]; 22%.…”
Section: Resultssupporting
confidence: 86%
“…The increase in C18:0 and CLA with LRS were probably associated with greater intake of PUFA and, therefore, greater rate of biohydrogenation (Table 2 shows FA profiles of CON and LRS diets). Fernández et al (2018) reported that lemon leaves contain 3% EE, with high concentrations of C18: 1n -9 cis, C18: 2n -6 cis, and C18: 3n -3, which are known for their antibacterial activities (Desbois and Smith, 2010). Atherogenicity and thrombogenic indices were calculated as indicated by Ulbricht and Southgate (1991), and from a human health standpoint the lower index of LRS compared with CON suggested higher quality.…”
Section: Romero Et Al: Dietary Citrus Leaves and Methane Emissionsmentioning
confidence: 99%
“…Therefore, as a substitute for assessing the model performance, we decided to compare CH 4 yield predicted using Equation (1) or using the relationship between CH 4 yield and the molar proportions of VFA (acetate, propionate and butyrate) in rumen fluid as described in recent research [27]. The results from nine studies (21 treatments and 187 individual observations) in the dataset that reported molar proportions of VFA in rumen fluid were used for the comparison [11][12][13][14][15][16]18,19,22]. The descriptive statistics of the variables used in the calculations and of the predicted CH 4 yields according to both methods are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Any treatment where CH 4 emission was manipulated by administering chemical additives to the animals was excluded. Twelve peer reviewed research papers that involved a total of 30 treatments with 223 individual observations fulfilled the requirements (Table 1) [11][12][13][14][15][16][17][18][19][20][21][22]. The experimental diets were very varied and included hays, silages, agro-industrial by-products, cereals, protein concentrates and fat sources.…”
Section: Methodsmentioning
confidence: 99%